EVIDENCE FOR THE INFLUENCE OF CONFUCIAN SOCIAL LEARNING THEORY ON NEGATIVE BEHAVIORAL OUTCOMES - Nicholas Lassi (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
This study is a test of Confucian social learning theory’s ability to influence negative behavioral outcomes among young people. Material relating to learning from different social environments and the attendant behavioral outcomes was filtered out of an assortment of Confucian texts, forming a limited Confucian social learning theory. Gang activity variables, representing levels of learned immorality within a community, from the NLSY97, were tested by delinquency and substance use outcome variables. The data was attained from the initial wave of responses from the NLSY97, with a sample of 8,985 people from the United States between the ages of 12-16. Confucian theory was supported by this examination, even after controlling for several variables including gender, ethnicity, age, household income, parent education, etc. The more gang activity (or immorality) within an environment, the greater the probability that one will be delinquent and engage in substance use. The more gang activity (or immorality) among close relatives or friends (people who are imitated or in near proximity), the greater the probability that one will be delinquent and engage in substance use. The more days gunshots are heard in a neighborhood per week (or serious immorality within a neighborhood), the greater the probability that one will be delinquent. This study attempts to bridge the gap between Confucian theory and modern criminological data, adding support to Confucian social learning theory